THE INFLUENCE OF ORGANIZATIONAL CULTURE, EDUCATION AND TRAINING ON EMPLOYEE PERFORMANCE - Atmoko, Agus Dwi (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2022)
The purpose of this study was to examine the influence of organizational culture, education, and training on employee performance at the Sawunggalih Aji Polytechnic, Purworejo Regency. Data analysis used research instrument analysis which included validity testing using product-moment correlation analysis, reliability testing using Cronbach's alpha technique, hypothesis testing using the rule of the analysis technique.The results showed that: 1) there was a positive and significant influence of organizational culture on employee performance, 2) there was a positive and significant effect of education and training on employee performance, 3) there was a positive and significant influence on organizational culture, education, and training on employee performance.This study uses linear regression analysis. The variables studied in this study were to examine the strength of the relationship and the magnitude of the influence of organizational culture, education, and training on employee performance. The research was conducted with the location and employees at the Sawunggalih Aji Polytechnic.The current condition of the Sawunggalih Aji Polytechnic still has limitations with various problems. The limitations experienced include financial capacity, limited access to information and technology. Therefore, literacy of Organizational Culture, Education, and Training improve performance. Several studies have been conducted to prove that literacy in Organizational Culture, Education, and Training has an impact on improving employee performance.This study offers interesting recommendations regarding organizational policies to increase work engagement and its dimensions. Based on the findings of this study, the direct effect of education and training, as well as organizational culture on performance is more dominant than the joint effect of each variable.